Uncertainty estimation of population doses from medical procedures. (September 2016) - Hourdakis, C.J.; Vogiatzi, S.; Economides, S.; Nikolaou, M.; Karfopoulos, K.; Kamenopoulou, V.
Abstract : Introduction: "Collective dose", S (person-Sv) and "average effective dose per person of population", Ēper-caput (mSv/caput) are useful indicators concerning population exposure to ionizing radiation. Estimation of relevant uncertainties is necessary for avoiding misleading interpretation of results. Purpose: This study presents the uncertainty estimation of the Greek population doses from medical procedures. The work was performed in the framework of 'PRISMA' project within GSRT's KRIPIS action, funded by Greece and the European Regional Development Fund of the EU under the O.P. Competitiveness and Entrepreneurship, NSRF 2007–2013. Materials and methods: S and Ēper-caput were assessed for 2014. The sources of uncertainty were identified and Type A or B uncertainty values were assigned, based on data sets for: (a) dosimetric quantity measurements, (b) patient average effective dose E (mSv) calculation per procedure, (c) procedure frequency and (d) extrapolation to countrywide scale. Results: E uncertainties ranged from 20% to 80% ( k = 1, ∼67% c.l.). S and Ēper-caput uncertainties were estimated 13% and 8% for diagnostic radiology and nuclear medicine procedures respectively and 12% for all medical diagnostic procedures ( k = 1, ∼67% c.l.). Conclusion: The large variety of medical diagnostic procedures resulted in high uncertainty for E. Nevertheless, S and Ēper-caput uncertainties appeared compressed. Reporting data on population exposure to ionizing radiation with the relative uncertainties increases the reliability of findings and conclusions. Disclosure: Authors have not any relationship that may bias this presentation.